DESIGN ANALYSIS AND IMPLEMENTATION OF A SOFTWARE FOR THE FORMULATION OF FOOD MIXTURES BASED ON ANDEAN CROPS: Design and analysis of a software for the formulation of food mixtures based on Andean crops - Arapa Carcasi, Percy (Revista Colombiana de Investigaciones Agroindustriales, 2020)
The use of software for engineering in different areas is increasing in order to make more efficient processes and thus, reduce costs in the products and services that a certain company produces. In the market, there is a variety of software for food mixtures formulation, but none with information of Andean products such as tarwi, cañihua, maca, quinoa, corn, kiwicha, which does not allow the application of the software for the formulation of food mixtures with Andean crops. The objective of this work was to develop application software that best approximates the results obtained in a laboratory to formulate food mixtures based on Andean crops. The application software "Formulation of Mixtures", the design of the prototype and the unit test of development were carried out applying the agile methodology XP (Extreme Programming). Software acceptance tests were carried out with the technique based on experience, with non-probability sampling, analyzing the results obtained previously with mixtures of Andean products and their derivatives such as wheat bread, cañihua cookies, quinoa-based drinks and other mixtures. food. With the use of the application software, it was determined that there are no significant differences between the results obtained in the laboratory with the results obtained using the application software for nutrient content and chemical computation.